Stokes parameter studies of spontaneous emission from chiral nematic liquid crystals as a one-dimensional photonic stopband crystal: Experiment and theory - Woon, K.L.; O'Neill, M.; Richards, G.J.; Aldred, M.P.; Kelly, S.M. (American Physical Society, 2005)
The helical structure of uniformly aligned chiral nematic liquid crystals results in a photonic stopband for only one sense of circular polarization. The spectroscopic Stokes polarimeter is used to analyze spontaneous emission in the stopband. Highly polarized photoluminescence is found and the polarization properties vary with the excitation wavelength. Spontaneous emission is enhanced at the stopband edge and this Purcell effect is greater on excitation at wavelengths where the absorption coefficient is low. This is interpreted as greater overlap between the excited molecules and the electrical modal field of the resonant modes at the stopband edge. Photoluminescence detected from the excitation face of the liquid crystal cell is less polarized because of photon tunneling. Fermi’s golden rule in conjunction with Stokes vectors is used to model the polarization of emission taking multiple reflections at the interfaces of the cell into account. The discrepancy between the experiment and the theoretical model is interpreted as direct experimental evidence that virtual photons, which originate from zero point fluctuations of quantum space, are randomly polarized.